A Case Report of Severe Mitral Regurgitation Due to Flail Posterior Mitral Leaflet - Piggott, Laura; Chinnéide, Ashling Ní; Worthington, Laura; Shiels, Paul (Cardiology and Cardiovascular Medicine, 2020)
Abstract not available in the source database.